Shattering the Glass Ceiling: Career Barriers and Opportunities for Women in Malaysia's Auditing Sector - Mat Samsudin, Mohd Amir; Arumugam, Aswini; Abidin, Shamharir; Ishak, Zuaini (2024)
Despite women comprising over 55% of chartered accountants in Malaysia, only 13%-22% attain partnership level. This discrepancy highlights the presence of the "glass ceiling," an invisible barrier preventing women from advancing in their auditing careers despite their qualifications, skills, and achievements. Our study explores this phenomenon through the lived experiences and perceptions of women in the auditing profession. We conducted semi-structured interviews with nine audit staff (current and former) from both the Big Four and non-Big Four firms. Analyzing the findings through the framework of inequality regimes theory, we identified three key themes that contribute to career stagnation: (i) work-life balance, (ii) individual challenges, and (iii) occupational minority status. Specific barriers include marriage, demanding work schedules, self-determination challenges, professional qualification requirements, occupational minority status, and language barriers